Asset-based approach to poverty reduction in Lithuania - Laurinavičius, Algimantas; Galinienė, Birutė (Technological and Economic Development of Economy, 2013)
This paper reviews the articles of Lithuanian authors on social policy topic and assesses if the asset-based policy topic was ever explored. It briefly analyses the efficiency of current social security policy in Lithuania and social-economical state of inhabitants. It states that in order to reduce poverty and inequality, current social policy should be reformed, and the current income support (or income security) policy should be replaced by the asset-based policy which stresses the development of skills, knowledge and capabilities, promotes savings, investments and building of assets and gives everyone a possibility to become a capital owner. The paper presents results of a representative survey which was aimed to explore Lithuanian inhabitants’ opinion towards the new form of social policy: asset-based policy. It uncovers that vast majority of Lithuania’s inhabitants would agree to the implementation of the asset-based policy, based on children’s savings accounts.